2023
DOI: 10.2147/rmhp.s395534
|View full text |Cite
|
Sign up to set email alerts
|

First-Aid Knowledge and Attitudes of Schoolteachers in Saudi Arabia: A Systematic Review

Abstract: Purpose Schoolteachers are the main people to provide first aid in cases of health-related emergencies during school hours. In this review, we aimed to synthesize teachers’ knowledge and attitudes about first aid in Saudi schools. Methods This systematic review was carried out in line with The Preferred Reporting of Items for Systematic Reviews (PRISMA) guidelines. PubMed (via MEDLINE), CINAHL, and the Cochrane databases were searched between January and March 2021. Stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 37 publications
1
4
0
Order By: Relevance
“…Studies conducted in Addis Ababa and Debre Tabor City, Ethiopia, also reported that more than half of the school health teachers lacked knowledge of first aid 4,19 . These findings are consistent with a previous systematic review that highlighted inadequate first-aid knowledge among school health teachers 21 . These findings imply that inappropriate knowledge of first aid among school health teachers may decrease the chances of children receiving appropriate and timely first aid, which could potentially increase the risk of complications after any incident in the school environment.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Studies conducted in Addis Ababa and Debre Tabor City, Ethiopia, also reported that more than half of the school health teachers lacked knowledge of first aid 4,19 . These findings are consistent with a previous systematic review that highlighted inadequate first-aid knowledge among school health teachers 21 . These findings imply that inappropriate knowledge of first aid among school health teachers may decrease the chances of children receiving appropriate and timely first aid, which could potentially increase the risk of complications after any incident in the school environment.…”
Section: Discussionsupporting
confidence: 93%
“…The first part included questions about the participant's demographic characteristics, including gender, age, education level, whether possessing a degree related to health sciences, years of experience in teaching, years of experience in school health services, previous nonprescription medicine training, previous first-aid training, number of teaching hours per week, and school health service period. The selection of these specific factors was based on previous studies 4, 7,13,14,[16][17][18][19][20][21][22][23][24][25] . The second part of the instrument included 30 questions on nonprescription medicine knowledge.…”
Section: Study Tool and Variablesmentioning
confidence: 99%
See 1 more Smart Citation
“…The importance of increasing teachers’ knowledge of first aid was asserted by Al-Harbi et al ,[ 19 ] Kanjo et al ,[ 17 ] Almuslim et al ,[ 22 ] and Alkhotani,[ 36 ] especially as mainstream schools in Saudi Arabia do not have nurses and teachers are not required to attend training courses on first aid. [ 35 ]…”
Section: Discussionmentioning
confidence: 99%
“…[ 35 ] Alsulami has pointed out that there is a lack of healthcare nurses in schools in Saudi Arabia, which indicates the importance of providing teachers with the knowledge and practice of providing first aid until medical help arrives. [ 35 ] Kanjo et al , Almuslim et al , and Alkhotani also supported this view. [ 17 22 36 ]…”
Section: Literature Reviewmentioning
confidence: 99%